2020
DOI: 10.1515/epoly-2020-0069
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing tribo-mechanical properties and thermal stability of nylon 6 by hexagonal boron nitride fillers

Abstract: Mechanical and tribological properties of nylon 6 and nylon 6/h-BN composites were investigated in this paper. Tensile, hardness, and impact tests were carried out for mechanical properties, while wear tests on pin-on-disc were carried out for tribological properties identification. Abrasion resistance tests were carried out on the TABER apparatus to analyze the abrasive wear of materials. SEM, XRD, and TGA were used to characterize the materials and to understand the distinctive features of nylon 6 and nylon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Similiarly, the study of Muralidhara et al [67] revealed that presence of hBN results in increment in mechanical properties of CF filled epoxy. Moreover, Randhawa and Patel [68] reported that tensile strength and modulus of PA 6 increased by 15.2% and 64.5%, respectively, after the addition of 8 wt.% hBN.…”
Section: Introductionmentioning
confidence: 97%
“…Similiarly, the study of Muralidhara et al [67] revealed that presence of hBN results in increment in mechanical properties of CF filled epoxy. Moreover, Randhawa and Patel [68] reported that tensile strength and modulus of PA 6 increased by 15.2% and 64.5%, respectively, after the addition of 8 wt.% hBN.…”
Section: Introductionmentioning
confidence: 97%
“…PP/ PA6 and PP/PA6/h-BN was found quite higher compared to pure PP because of the presence of hard PA6 material. While comparing Batch B and Batch C, it was found that Batch C was having lower COF compared to Batch B owing to the formation of the self-lubricating film which reduced (Yi and Yan, 2006;Randhawa and Patel, 2020a, 2020b, 2020c the COF of composite material compared to the PP/PA6 blend as shown in Figure 10.…”
Section: Effect Of Hexagonal Boron Nitride Particles On Wear Propertiesmentioning
confidence: 98%
“…Carbon nanotubes (CNT) were found effective in improving COF and wear resistance of the PP/CNT composite (Gandhi et al, 2013) compared to pure PP. The addition of 2 wt.% boric anhydride to the PA6 matrix (Randhawa and Patel, 2020a, 2020b, 2020c enhanced the tensile strength and abrasion resistance of the PA6/boric anhydride composite, and the hardness was found gradually enhanced as the boric anhydride filler percent increase in the PA6 matrix. The 2 wt.% titanium dioxide (TiO 2 ) fillers provided the best tribological performance (Guglani and Gupta, 2018) of PA66/TiO 2 composite.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Boron based compounds, i.e. diboron trioxide (Randhawa and Patel, 2020a, 2020b, 2021a and hexagonal boron nitride (Randhawa and Patel, 2020a, 2020b, 2021a, 2020bMistry and Randhawa, 2020;Möller et al, 2002;Martin et al, 1992;Vyas and Randhawa, 2021) are having excellent solid lubricant properties, while boron carbide (Cuong et al, 2006;Erdemir et al, 1996) is an excellent wear-resistant material. The tribo-oxidation of hexagonal boron nitride in the presence of water leads to the formation of boron oxide.…”
Section: Particle Reinforced Polymer Composites and Hybrid Compositesmentioning
confidence: 99%